Experimental study on reduction of pollutant emissions in reactivity controlled compression ignition (RCCI) engine fueled with diesel/gasoline fuels - Fırat, Müjdat; Altun, Şehmus; Okcu, Mutlu; Varol, Yasin; Şenocak, Melih Şafak (Murat CİNİVİZ, 2022)
Reactivity Controlled Compression-Ignition (RCCI) concept presents a great potential to reduce both NOx and soot emissions from conventional diesel engines with improved thermal efficiency. Therefore, in this work, a single-cylinder diesel engine with CRDI was operated on RCCI mode. To investigate the effect of RCCI mode on engine performance and emissions, gasoline was injected into the port as LRF, while diesel was injected directly into the cylinder as HRF. Premixed ratio of low reactivity fuel was varied from 0% (conventional diesel mode, CDM) to 60% with 15% intervals as energy ratio given to engine per cycle. Engine load was also studied from 20% to 60% of max. engine torque with 20% intervals to stimulate low, mid and mid-high load conditions. Experimental results showed that with increase of Rp, unburned HC and CO emissions increased while smoke opacity decreased significantly (up to about 95% in case of 0.60 Rp and 60% engine load) in gasoline/diesel RCCI compared to CDM. Though NOx emissions decreased at low engine loads with RCCI strategy, they started to increase with increase of Rp at high loads.
Keywords: Engineering; Mühendislik